Nanocrystals and amorphous matrix phase studies of Finemet-like alloys containing Ge - Moya, Javier Alberto (2010)
Two simple models were developed in order to determine the chemical composition of both nanocrystals and intergranular amorphous phases in nanocrystallized Fe73.5Si13.5B9Nb3Cu1 containing Ge using data from X-ray diffraction and Mössbauer spectroscopy techniques. Saturation magnetization of the amorphous intergranular matrix (Msam) was calculated considering the contribution of the α-Fe(Si,Ge) nanocrystals and saturation magnetization of the alloys. The behavior of Msam with the iron content of the matrix was obtained and discussed. The exchange stiffness constant for the nanograins and for the amorphous phases was determined. The increment in the coercive field (Hc) with increasing Ge content was evaluated using two theoretical models for the random magnetocrystalline anisotropy constant (〈K1〉). Results show that the magnetic hardening observed could not be attributed to an increase in 〈K1〉 but mainly to an important increment of the magnetostriction constant of the α-Fe(Si,Ge) nanocrystals (λscr). Values for λscr are proposed.